2016
DOI: 10.3847/1538-4357/833/2/198
|View full text |Cite
|
Sign up to set email alerts
|

Master Optical Polarization Variability Detection in the Microquasar V404 Cyg/Gs 2023+33

Abstract: On 2015 June 15 the Swift space observatory discovered that the Galactic black hole candidate V404 Cyg was undergoing another active X-ray phase, after 25 years of inactivity (Barthelmy et al. 2015). Twelve telescopes of the MASTER Global Robotic Net located at six sites across four continents were the first ground based observatories to start optical monitoring of the microquasar after its gamma-ray wakeup at 18h 34m 09s U.T. on 2015 June 15 . In this paper we report, for the first time, the discovery of vari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…As shown in Fig. 1 of Lipunov et al (2016), the polarization change is anticorrelated with flux change.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…As shown in Fig. 1 of Lipunov et al (2016), the polarization change is anticorrelated with flux change.…”
mentioning
confidence: 77%
“…Tanaka et al (2016) observed V404 Cyg at various epochs between MJD 57190-57194 and did not find any evidence of intrinsic optical or NIR linear polarization, or any significant change in the amount of polarization or the polarization position angle. However, observations made between MJD 57191.62-57191.84 using the MASTER robotic telescope network showed a 4%-6% change in the optical linear polarization (Lipunov et al 2016). As shown in Fig.…”
mentioning
confidence: 91%
“…Infrared polarization has now been detected from several quiescent, outbursting, and persistently accreting black hole binaries, lending credence to this expectation (Russell & Fender 2008;Russell & Shahbaz 2014;Russell et al 2016;Chaty, Dubus, & Raichoor 2011). Unfortunately, here too the observational evidence is equivocal with some studies finding variable polarization, and others not, and characteristics that may be more consistent with scattering in a disc outflow rather than from jet synchrotron emission (Tanaka et al 2016;Lipunov et al 2016;Shahbaz et al 2016;Itoh et al 2017;Kosenkov et al 2017).…”
Section: Are Slow Variations Driven By Plasmon Ejections or Disc Irramentioning
confidence: 92%
“…A lack of optical and near-infrared polarisation was reported by Tanaka et al (2016) in two periods during the outburst. There was, however, evidence of a strong contribution of synchrotron emission related to jet ejections in some other epochs (Rodriguez et al 2015;Martí et al 2016;Shahbaz et al 2016;Lipunov et al 2016;Bernardini et al 2016b). Gandhi et al (2016) found subsecond optical flaring events and proposed that not only Xray reprocessing but also non-thermal emission contributed to them.…”
Section: Introductionmentioning
confidence: 99%